PROJECT-BASED LEARNING (PBL) METHODS ARE ABLE TO IMPROVE PMKR LEARNING ACHIEVEMENTS LEVEL XII KRIAN 2 SIDOARJO VOCATIONAL SECONDARY SCHOOL - basuki, aryanto (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Negeri Semarang, 2023)
Starting from an anxiety I have as an educator in a private school, namely at SMK KRIAN 2 SIDOARJO that students are currently experiencing a decrease in learning outcomes and interest in learning. This result occurs because the teacher still provides a conventional learning model where the teacher just explains in the workshop and students immediately carry out the practice so that students do not understand in detail even though they have been given job sheets or are active in practice. This type of research is Classroom Action Research (PTK) proposed by Kemmis Taggart. This research model includes four steps, namely planning, implementation, observation, and evaluation through a number of periods. The results of period 1 show known student learning achievements whose average pretest score in cycle 1 reached 39.58, with a number of students successfully achieving or exceeding KKM scores. And in cycle 2, the average pretest score reached 50.00, with only 14.81% of the number of students who managed to reach or exceed the average KKM score. The posttest score reached 88.19%